Evaluasi Penerapan Pembelajaran K13 di Sekolah Dasar Dharmawati Arief Tangerang - Ina Magdalena; Nia Hidayatul Maula; Sekar Ayu Amelia; Amelia Ismawati (MANAZHIM, 2020)
Evaluation is interpreted as a process of collecting systematic analysis and interpretation to determine the extent which students that achieve the learning objectives as stated in curriculum. Curriculum evaluation is intended to examine the overall curriculum performance in terms of various criteria. Performance indicators that are evaluated are not only limited to effectiveness, but also the relevance, efficiency of this program. This research uses qualitative research by using description interviews as a data collection technique. The results show that in this application, teachers still found experience difficulties in the process of learning activities due to lack of optimal teacher training. The implementation of the K13 curriculum was carried out within one week, and only a few teachers took part in the training so that there were no equal teachers who were able to apply the K13 curriculum in the process of teaching activities in primary schools